Bone Quality in Diabetes - Saito, Mitsuru; Marumo, keishi (Frontiers in Endocrinology, 2013)
Diabetes is associated with increased risk of fracture, although type 2 diabetes is characterized by normal bone mineral density (BMD). The fracture risk of type 1 diabetes increases beyond an explained by a decrease of BMD. Thus, diabetes may be associated with a reduction of bone strength that is not reflected in the measurement of BMD. Based on the present definition, both bone density and quality, which encompass the structural and material properties of bone, are important factors in the determination of bone strength. Diabetes reduces bone quality rather than BMD. Collagen cross-linking plays an important role in bone strength. Collagen cross-links can be divided into lysyl hydroxylase and lysyl oxidase-mediated enzymatic immature divalent cross-links, mature trivalent cross-links and glycation- or oxidation-induced non-enzymatic cross-links (Advanced Glycation End products: AGEs) such as pentosidine. These types of cross-links differ in the mechanism of formation and in function. Not only hyperglycemia, but also oxidative stress induces the reduction in enzymatic beneficial cross-links and the accumulation of disadvantageous AGEs in bone. In this review, We describe the mechanism of low bone quality in diabetes.